Besteuerung von künstlicher Intelligenz und deren Implikationen auf die Besteuerung der Digitalwirtschaft - Lemm, Timo (Steuerwissenschaftliche Schriften, 2023)
The work deals with "Paying with data" from a VAT perspective. Starting from the (tax) legal classification of artificial intelligence, the effects of the use of artificial intelligence in business models on the existing taxation system are presented and the current political reform proposals are examined. Based on this, an own solution approach for a "fair" taxation of the digital economy within the framework of VAT law is developed. In this context, a separate valuation option is derived, taking into account tax law and economic valuation methods, and reform proposals are put forward for both national and EU VAT law.